(untitled) (E Global Congress, 2025)
The article addresses the issue of developing creative activity in primary school students during reading literacy lessons. It analyzes the psychological, pedagogical, and methodological foundations for fostering a creative approach to working with texts in primary education. The paper presents principles, techniques, and technologies that stimulate students’ reading and creative engagement. Based on practical experience, the effectiveness of integrating creative tasks and innovative approaches into the educational process is substantiated. The article concludes that the formation of a reader’s personality is essential for the overall and speech development of the child.